Advanced electron cyclotron heating and current drive experiments on the stellarator Wendelstein 7-X - Stange Torsten; Laqua Heinrich Peter; Beurskens Marc; Bosch Hans-Stephan; Bozhenkov Sergey; Brakel Rudolf; Braune Harald; Brunner Kai Jakob; Cappa Alvaro; Dinklage Andreas; Erckmann Volker; Fuchert Golo; et al. (EPJ Web of Conferences, 2017)
During the first operational phase (OP 1.1) of Wendelstein 7-X (W7-X) electron cyclotron resonance heating (ECRH) was the exclusive heating method and provided plasma start-up, wall conditioning, heating and current drive. Six gyrotrons were commissioned for OP1.1 and used in parallel for plasma operation with a power of up to 4.3 MW. During standard X2-heating the spatially localized power deposition with high power density allowed controlling the radial profiles of the electron temperature and the rotational transform. Even though W7-X was not fully equipped with first wall tiles and operated with a graphite limiter instead of a divertor, electron densities of n e > 3·1019 m-3 could be achieved at electron temperatures of several keV and ion temperatures above 2 keV. These plasma parameters allowed the first demonstration of a multipath O2-heating scenario, which is envisaged for safe operation near the X-cutoff-density of 1.2·1020 m-3 after full commissioning of the ECRH system in the next operation phase OP1.2.